Automatic Control Synthesis for Agents and Their Cooperation in MAS - Čapkovič, František (Computing and Informatics, 2012)
Automatic synthesis of control for a kind of DES (discrete-event systems) is discussed and an approach to it is proposed and presented. The approach consists in the proposal of the control synthesis procedure based on bipartite directed graphs yielding both the feasible control trajectories and the corresponding state ones. Soundness of the approach is tested on examples. Then, the usage of the approach is combined with the supervisor synthesis in order to complement it. Applicability of such approach is demonstrated by means of several illustrative examples of both the single agents and the agent cooperation in MAS.